Fine-tuning CO2 separation of mixed matrix membranes by constructing efficient transport pathways through the addition of hybrid porous 2D nanosheets - Adel Hosseinkhani; Mohammadreza Omidkhah; Abtin Ebadi Amooghin (Chemical Engineering Journal Advances)
In this research, the effect of adding PEG 400 and synthesized rGONiO hybrid nanocomposite to Pebax® to design the Pebax® 1657/PEG 400/rGONiO ternary mixed matrix membrane (MMM) for CO2/CH4 and CO2/N2 separation, has been evaluated. For this purpose, neat membrane, Pebax® 1657/PEG 400 blend membranes and Pebax® 1657/PEG400/rGONiO based MMMs were fabricated. In the next step, gas separation performance tests were performed on the membranes at 35 °C and operating pressure of 2 to 10 bar, and gas separation properties were evaluated. Also, FTIR-ATR, XRD, FESEM, DSC, TGA, TEM, and tensile analyses were employed. The obtained results indicate the uniform dispersion of rGONiO nanocomposite in the polymer matrix and the proper adhesion between rGONiO nanocomposite and polymer chains due to the modification of the hydrophilicity by polyethylene glycol (PEG), which led to the preparation of a ternary MMM without defects. It significantly improved the separation performance of the membranes compared to the neat membrane. Gas permeability results demonstrated that the optimized blend membrane was obtained at 30 wt.% of PEG 400, and the optimized ternary MMM was obtained at 30 wt.% of PEG 400 and 0.75 wt.% of rGONiO. Pebax® 1657/PEG (30 wt.%)/rGONiO (0.75 wt.%) with CO2 permeability of 442.37 barrer showed 258 % improvement compared to the neat membrane at 10 bar Moreover, the excellent CO2/CH4 and CO2/N2 selectivity of 121.32 (495.29 % improvement) and 510.45 (713.59 % improvement) were reported for the optimized ternary MMM, respectively. Finally, the fabricated membranes surpassed Robeson's upper bound limit, indicating their potential for real gas separation situations.